Lake Bottom Relief Condition Based on Bathymetry Measurement in Labuan Cermin Lake, East Kalimantan - Muhammad Yaser MF; Iwan Suyatna; Paulus Taru; Noorsheha Noorsheha (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Biduk-biduk sub-district in East Kalimantan Province is famous for its natural beauty and richness in its waters, one of which is Labuan Cermin Lake. This study aims to determine the basic depth conditions of the waters of Lake Labuan Cermin and determine the type or type of tide. The implementation of the research includes data collection which is divided into 2, namely, data on the condition of the bottom of the waters using bathymetry and data on changes in water levels (tides). Lake area data is obtained using satellite image data processing methods (mapping or GIS programs), then ground-checking is carried out through marking coordinate points (marking) or tracking the edge of the lake using GPS. Furthermore, depth data collection is carried out by measuring the bathymetry of various points scattered throughout the lake waters. Tidal data collection begins with the installation of a scale pole (tidal palm) at the location of the lake waters. Tidal data is obtained from observations of the water level/face read on the scale pole. The results of the study obtained that Labuan Cermin Lake waters have different slopes on each side of the lake. The southern part which is near the source of fresh water springs with a depth of 10 meters is categorized as steep with a slope of 32.56% or 18.03o, the bottom of the lake waters is categorized as sloping or undulating with a percentage of 7.58% or 4.33o. The result of the type of tide in the waters of Lake Labuan Cermin is a mixed type leaning to double daily.